STRATEGI QUEEN CARD DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN PENDEKATAN SAINTIFIK - Siti Dawiyah Farichah (EL-Islam, 2021)
Teachers are required to have the ability to regulate in general the components of learning in such a way so that there is a link between the functions of the intended learning components. To carry out tasks professionally, teachers need solid insight into the possibilities of teaching and learning strategies that are following the learning objectives that have been formulated. The focus of the research is: (1) How is the implementation of the Queen Card strategy in PAI learning with a scientific approach at Baitul Izza Nganjuk Middle School, (2) What are the supporting and inhibiting factors for implementing the Queen Card strategy in PAI learning with a scientific approach at Baitul Izza Nganjuk Middle School, and ( 3) What are the results of implementing the Queen Card strategy in PAI learning with a scientific approach at Baitul Izza Nganjuk Middle School. The aims of this researcher are (1) to describe the implementation of the Queen Card strategy in PAI learning with a scientific approach at Baitul Izza Nganjuk Middle School, (2) to describe the supporting and inhibiting factors for implementing the Queen Card strategy in PAI learning with a scientific approach at Baitul Izza Junior High School. Nganjuk, and (3) To find out the results of the implementation of the Queen Card strategy in PAI learning with a scientific approach at Baitul Izza Nganjuk Middle School. The research approach in this thesis is qualitative-descriptive, data collection techniques using three methods, namely interviews, observation, and documentation. While checking the validity of the data using source and technique triangulation, data analysis used is data condensation; includes selecting, focusing, simplifying, abstracting, transforming; data presentation; then verify and draw conclusions. Following the results of the study, the Queen Card strategy in PAI learning with a scientific approach at Baitul Izza Nganjuk Middle School, namely, (1) Implementation of implementing the Queen Card strategy in PAI learning such as adjusting subject matter with learning strategies, discussion and evaluation of learning using strategies Queen Card. (2) The supporting and inhibiting factors, the main supporting factors are a comfortable and calm school environment and support from the principal in the form of providing school facilities such as libraries. While the inhibiting factor is the lack of discipline and interest in student learning. (3) The result of the implementation of the Queen Card strategy is that student activity, relationships or interactions with friends or teachers go well and get good marks in the learning process